(untitled) (Journal of the College of Basic Education, 2022)
The model, Epicauta hirticornis Haag-Rutenberg, was chosen because it represents the characteristics of the family Meloidae. And I studied the main parts of the body, which are the head, thorax, abdomen and their appendices, in order to evaluate the structures of the external appearance and the extent of dependence on them in the classification of species.It is considered one of the agricultural pests of the alfalfa crop, as it lives in clusters. It also has medical importance because it contains cantharidin, which is used in the treatment of many diseases, including cancer.